Comparing dietary guidelines indices between women with chronic diseases and healthy women: a cross-sectional study: Diet quality and chronic diseases - Aljadani, Haya (Progress in Nutrition, 2022)
Abstract. Background and aim: There is widespread recognition that many chronic diseases seen today are related to physical inactivity and poor dietary choices. Most dietary guidelines were based on safe eating habits to safeguard against malnutrition and the emergence of poor diet-linked illnesses. The present study aimed to compare the dietary guidelines index (DGI) scores in women with chronic diseases and healthy women.Methods: The information in this study was collected through a questionnaire distributed to the Saudi community from January 2020 to February 2021. The inclusion criteria include all women with and without chronic diseases. The DGI data obtained from a tool developed based on the valid short semi food-frequency questionnaire (FFQ), valid food-based New Zealand diet quality index (NZDQI), Saudi dietary guidelines (SDG), and American dietary recommendation (ADR).Results: 879 women filled out this questionnaire; 12.8% of them are women with chronic diseases, whereas healthy women constitute 87.2%. The results revealed that women with chronic diseases had a significantly higher fruit score (p < 0.05) and vegetable score (p < 0.01) compared to the healthy women. The findings also indicated that women with chronic diseases who are overweight or obese and not engaged in physical activity showed significantly (p < 0.05) higher total DGI scores compared to women without chronic diseases who are overweight or obese and not engaged in physical activity. In contrast, there is no significant difference in DGI score between the women with chronic diseases with normal BMI and engaged in physical exercise and their healthy counterparts.Conclusions By excluding the physical activity factor and the healthy BMI, women with chronic diseases adopt healthy dietary systems compared to healthy women.